Game Methods of Active Learning - qizi, Xidirova Umida Islom (Researchparks Publishing, 2023)
The article highlights the urgent problems of modernization and improvement of the quality of teaching English. Particular attention is paid to the characteristics of the most effective methods of teaching English in higher education. The implementation of this idea is impossible without development and introduction of appropriate learning technologies. Higher education should not be preparation for life, higher education should be life itself.